The July war and its effects on Lebanon’s power-sharing - Fakhoury, Tamirace (2007)
This paper examines Lebanon’s fragile politics of accommodation in the wake of the Hezbollah-Israeli war in July 2006. After drawing attention to the dangerous emergence of a bipolar and unstable power-sharing model between Lebanese dissenting factions, it shows how a flimsy elite consensus, divergent perceptions of external threat, the republic’s entanglement in the regional and international orbits as well as the increase of foreign pressures since the 2005 Beirut Spring could impede the pacification of a divided society. In the end, the author explains how a non-aligned foreign policy could help Lebanon pacify its internal cleavages and extricate itself from the dilemma of polarized powersharing. On a broader scale, this article helps shed light on the dilemma of power-sharing systems on stormy seas when external conflicts overlap with internal conflict lines.